2017
DOI: 10.1016/j.clinbiochem.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Defect in dermatan sulfate in urine of patients with Ehlers-Danlos syndrome caused by a CHST14/D4ST1 deficiency

Abstract: This is the first study to perform a urinary disaccharide compositional analysis of chondroitin sulfate (CS)/DS chains in patients with EDS caused by a CHST14/D4ST1 deficiency, and demonstrated the absence of DS chains. This result suggests systemic DS depletion in this disorder, and also proposes the usefulness of a urinary disaccharide compositional analysis of CS/DS chains as a non-invasive screening method for this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…This makes GAGs key modulators in many diseases, giving them potential therapeutic applications. For example, heparan sulfate (HS) is released during sepsis and induces septic shock [18,19]; the removal of chondroitin sulfate (CS) may enhance memory retention and slow neurodegeneration in patients with Alzheimer's disease [20][21][22]; and dermatan enhance memory retention and slow neurodegeneration in patients with Alzheimer's disease [20][21][22]; and dermatan sulfate (DS) deficiency has been implicated in Ehlers-Danlos syndrome, thus the screening of DS in urine could be used as an early diagnostic tool [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…This makes GAGs key modulators in many diseases, giving them potential therapeutic applications. For example, heparan sulfate (HS) is released during sepsis and induces septic shock [18,19]; the removal of chondroitin sulfate (CS) may enhance memory retention and slow neurodegeneration in patients with Alzheimer's disease [20][21][22]; and dermatan enhance memory retention and slow neurodegeneration in patients with Alzheimer's disease [20][21][22]; and dermatan sulfate (DS) deficiency has been implicated in Ehlers-Danlos syndrome, thus the screening of DS in urine could be used as an early diagnostic tool [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…All of these functions allow GAGs to modulate disease. For example, hyaluronan can predict disease outcome and is used as a treatment for osteoarthritis [ 18 , 19 ]; deficiency of dermatan sulfate has been linked to Ehlers-Danlos syndrome, so screening of dermatan sulfate in urine may present a method of diagnosis [ 20 , 21 ]; reduced cerebral cell keratan sulfate levels have been implicated in Alzheimer’s disease [ 22 ]; and heparan sulfate has been shown to induce septic shock [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested a systemic depletion of DS in patients with mcEDS-CHST14; thus we presume that our urinary disaccharide analysis method can be implemented to allow a non-invasive screening for mcEDS-CHST14 [30]. established a urinary disaccharide analysis of CS/DS chains through an anion-exchange chromatography after treatment with DS-specific degrading enzymes; this analysis method showed that no DS was present in the urine of eight patients with mcEDS-CHST14 [30]. This result suggested a systemic depletion of DS in patients with mcEDS-CHST14; thus we presume that our urinary disaccharide analysis method can be implemented to allow a non-invasive screening for mcEDS-CHST14 [30].…”
Section: Glycobiological Findingsmentioning
confidence: 88%
“…Thus, impaired 4-O-sulfation inhibition due to D4ST1 deficiency enables back-epimerization from L-iduronic acid (IdoUA) to D-glucuronic acid (GlcUA) ( Figure 3E) [4,6,7]. In our laboratory, we have established a urinary disaccharide analysis of CS/DS chains through an anion-exchange chromatography after treatment with DS-specific degrading enzymes; this analysis method showed that no DS was present in the urine of eight patients with mcEDS-CHST14 [30]. This result suggested a systemic depletion of DS in patients with mcEDS-CHST14; thus we presume that our urinary disaccharide analysis method can be implemented to allow a non-invasive screening for mcEDS-CHST14 [30].…”
Section: Glycobiological Findingsmentioning
confidence: 99%
See 1 more Smart Citation